The Concept of Fitrah of Harry Santosa: An Alternative Concept of Islamic Education Based on Fitrah Syamilah - Suraiya Suraiya; Zubaidah Zubaidah; Abdul Manan; Salami Mahmud; M Nur Akhyar (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The growing demand for holistic Islamic education has renewed attention to fitrah as a possible foundation for understanding human development and educational purpose. This study examines Harry Santosa’s conception of fitrah syamilah, explores how it is constructed into a model of Islamic education, and critically assesses its strengths and limitations. The study employed qualitative literature research with a descriptive-analytical approach. Primary data were drawn from Santosa’s works, particularly Fitrah Based Education and Fitrah Based Life, while secondary sources were used to provide broader perspectives on fitrah and Islamic education. Data were collected through documentation and analyzed using content analysis, internal coherence analysis, idealization, and critical analysis. The findings show that Santosa understands fitrah as a comprehensive system that brings together fitrah munazzalah, the fitrah of nature, the fitrah of life, and diverse dimensions of human fitrah. This perspective shifts education from an externally driven process toward an inside-out orientation that seeks to recognize, nurture, and direct innate potential in accordance with revelation and the realities of life. The framework is particularly strong in its holistic orientation, developmental sensitivity, personalization, and integration of spiritual and human dimensions, although its practical application depends heavily on the understanding and involvement of parents and educators. The study further develops Theocentric-Humanist Education as a conceptual synthesis of fitrah syamilah that connects divine guidance, human potential, and civilizational responsibility